2013
DOI: 10.1111/fpa.12007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rivalry on Rivalry: Accommodation and the Management of Threats

Abstract: The paper investigates how states manage multiple rivalries when faced with immediate threats. We argue that accommodation of one rival allows states to shift resources from the management of another rival to deal with the costs of immediate threats. By examining enduring rivalries from 1966 to 1999, we show that states' reliance on accommodation in response to threats varies depending on the number of severe threats and the relative capabilities between the states and the threat‐issuing rivals. Findings show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Secondly, the study of international rivalries has so far hardly paid any attention to environmental factors and especially environmental cooperation (Rasler et al 2013), but would be well advised to do so. Contrary to realist theory, which is still very popular in this research field (Akcinaroglu et al 2014), such cooperation can facilitate reconciliation and eventually rivalry termination, if only to a certain degree and in certain contexts.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Secondly, the study of international rivalries has so far hardly paid any attention to environmental factors and especially environmental cooperation (Rasler et al 2013), but would be well advised to do so. Contrary to realist theory, which is still very popular in this research field (Akcinaroglu et al 2014), such cooperation can facilitate reconciliation and eventually rivalry termination, if only to a certain degree and in certain contexts.…”
Section: Discussionmentioning
confidence: 86%
“…Research has so far identified a number of factors facilitating rivalry termination (and hence more peaceful international relations), such as additional threats emerging for the involved states (Akcinaroglu et al 2014), systemic shocks (Rasler et al 2013) and economic recession in at least one of the respective countries (Clary 2015). But with a few exceptions, the theoretical frameworks underlying such studies usually emphasise threats to national security, state capabilities and regime survival, hence broadly fitting a realist theoretical framework (Prins and Daxecker 2008;Rasler et al 2013).…”
Section: Situating Environmental Peacemaking and Environmental Peacebuildingmentioning
confidence: 99%
“…We identify rivals using the expanded Diehl and Goertz rivalry dataset produced by Klein et al (2006). While there is an extant debate over the definition of rivalry, we use their definition as it offers a clear set of breakpoints for the end and beginning of rivalry based on MID interaction-ultimately the event that matters for our asymmetric dyads (Akcinaroglu et al 2013;Lu and Thies 2013).…”
Section: Measuring Neighboring Rival Parity and Disparitymentioning
confidence: 99%
“…The number of territorial disputes in which a country is involved at a certain point in time is therefore an important characteristic of that state, one that affects its approach to peaceful resolution of any individual dispute. Indeed, recent literature has shown that the number (Melin and Grigorescu ) and relative salience (Akcinaroglu, Radziszewski, and Diehl ) of states’ ongoing disputes impacts their behavior in a particular dispute. Based on these arguments we hypothesize that:
H 3 : The more disputes states are simultaneously involved in, the less likely they are to seek peaceful resolution to one such dispute through an IO.H 3A : The more disputes states are simultaneously involved in, the more likely they are to seek peaceful resolution to one such dispute through a state third party than through an IO.H 3B : The more disputes states are simultaneously involved in, the less likely they are to seek peaceful resolution to one such dispute through a third party than through bilateral negotiations.
…”
Section: Theorymentioning
confidence: 99%
“…Th e number of territorial disputes in which a country is involved at a certain point in time is therefore an important characteristic of that state, one that aff ects its approach to peaceful resolution of any individual dispute. Indeed, recent literature has shown that the number (Melin and Grigorescu 2014 ) and relative salience (Akcinaroglu, Radziszewski, and Diehl 2014 ) of states' ongoing disputes impacts their behavior in a particular dispute. Based on these arguments we hypothesize that: H 3 : Th e more disputes states are simultaneously involved in, the less likely they are to seek peaceful resolution to one such dispute through an IO.…”
Section: International Organizations As Multilateral Forumsmentioning
confidence: 99%